2014
DOI: 10.1007/s00221-014-3887-z
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and perceptual updating: correlated impairments in right brain injury

Abstract: It has been hypothesized that many of the cognitive impairments commonly seen after right brain damage (RBD) can be characterized as a failure to build or update mental models. We (Danckert et al. in Neglect as a disorder of representational updating. NOVA Open Access, New York, 2012a; Cereb Cortex 22:2745-2760, 2012b) were the first to directly assess the association between RBD and updating and found that RBD patients were unable to exploit a strongly biased play strategy in their opponent in the children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 75 publications
4
33
1
Order By: Relevance
“…The hypothesis that brain injury might impair statistical learning after right hemisphere damage is consistent with our prior data on tracking environmental regularities in patients with stroke (Shaqiri and Anderson, 2012; Shaqiri et al, 2013; Stöttinger et al, 2014a,b). However, other data suggests that either hemisphere could be important.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The hypothesis that brain injury might impair statistical learning after right hemisphere damage is consistent with our prior data on tracking environmental regularities in patients with stroke (Shaqiri and Anderson, 2012; Shaqiri et al, 2013; Stöttinger et al, 2014a,b). However, other data suggests that either hemisphere could be important.…”
Section: Introductionsupporting
confidence: 89%
“…It is plausible that this result reflects the prevalence with which this territory is damaged by cerebrovascular accidents (Mah et al, 2014). However, it should also be noted that in people without brain damage, nearby and connected areas of this region have been found to be active during tasks that require statistical and perceptual representations (Craig, 2009; Menon and Uddin, 2010; Stöttinger et al, 2014b). Previous studies have also implicated this region in speech production (for a review see Ackermann and Riecker, 2004) with higher activation also evident in this region in bilingual participants.…”
Section: Resultsmentioning
confidence: 99%
“…This task can be used among challenging participant populations, including young children, healthy seniors, and brain-damaged patients (Stöttinger et al 2014;Stöttinger et al 2013). Given the simplicity and wide variety of the picture sets, the task will be of interest to a broad range of research domains in psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies using picture sets that morph from one unique object (e.g., a rabbit) to another (e.g., a duck), with various levels of ambiguity in between, have shown that pictures are perceived categorically (i.e., as either a duck or a rabbit, but not as an alternate, third object representing the gradual merging of both; Hartendorp et al 2010;Newell & Bülthoff, 2002;Verstijnen & Wagemans, 2004). Also, it has been demonstrated that the ability to switch between two identities in a morphing continuum can be significantly impaired in autism spectrum disorder (Burnett & Jellema, 2013) and after brain damage to the right hemisphere (Stöttinger et al 2014). Studies have also used morphing sequences in fMRI studies to investigate the neural correlates of perceptual decisions in a gradually changing environment (Heekeren, Marrett, Bandettini, & Ungerleider, 2004;Thielscher & Pessoa, 2007).…”
mentioning
confidence: 99%
“…In this task, an animal (e.g., a duck) morphs over 15 iterations into another animal (e.g., a rabbit) with picture #8 depicting a well-known ambiguous figure (e.g., duck-rabbit, Wittgenstein, 1953). This picture morphing task (Stöttinger et al, 2014; see also Burnett & Jellema, 2013) measures how many morphs participants need before they switch to the new interpretation (i.e., rabbit). Unlike in previous studies, children were not informed about the content of the second interpretation, only about its potential for another interpretation.…”
Section: Introductionmentioning
confidence: 99%